Retraction Note: Understanding the essence of immersive marketing for educational services and knowledge transfer - Artyukhova Nadiia; Artyukhov Artem; Rehak Robert; Lyeonov Serhiy (E3S Web of Conferences)
The authors have expressed the wish to retract this article on the grounds that the list of references is incorrect. The Publisher and Editor(s) approved to the retraction.